What Drives Capital Financing in Europe? Evidence from Listed Firms in Germany - Salih, Kaiwan Hasan; Sangawi, Shakhawan Saeed; Salih, Rebwar Hussein (International Journal of Engineering and Management Sciences, 2025)
This article analyzed the factors that affect the capital financing of German non-financial corporations listed on the German Stock Exchange from 2017 to 2021. By applying a panel data regression model and the Generalized Least Squares (GLS) approach, the results show that the debt-to-assets ratio, equity multiplier, and long-term debt ratio are significantly impacted negatively by profitability as determined by the assets return. Firm size is positively correlated with both the equity multiplier and the long-term debt ratio, suggesting that larger companies use more long-term debt. Growth has a significant positive impact on the equity multiplier and long-term debt ratio but has little influence on the debt-to-assets ratio. Long-term debt is unaffected by liquidity, although the debt-to-assets ratio and equity multiplier are adversely impacted. The GMM method is used during the robustness check, and the findings are consistent with the major GLS findings. These results highlight how important firm-specific factors are in influencing choices about financial structure. The results of this research may be used as a guide for companies operating in Europe and offer valuable information about how to optimize capital structures in various financial contexts. Policymakers could also use the results of this investigation as a reference for creating financial laws and regulations that facilitate non-financial enterprises’ access to financing and effective capital allocation.